Adsorption and decomposition of methanol on gallium oxide polymorphs - Collins, Sebastián Enrique (2008)
The adsorption of methanol was studied on three gallia polymorphs (alpha, beta, and gamma), pretreated under oxygen or hydrogen at 723 K. Their Brunauer-Emmett-Teller surface areas were in the range 12-105 m2 g-1. Methanol (or methanol-d3) chemisorbs on the gallium oxides both molecularly, as CH3OHS (or CD3OHS,) and dissociatively, as methoxy (CH3O or CD3O) species, at 373 K. The quantification of the total amount of chemisorbed methanol at this temperature allowed us to determine the number of available surface active sites per unit area (NS), which is in the range 1-2 µmol m-2 for the oxygen pretreated oxides at 723 K. The density of active sites was moderately smaller (~25%) after pretreating the oxides under hydrogen at 723 K. The temperature-programmed surface reaction of adsorbed methanol and methoxy was followed by mass spectrometry and infrared spectroscopy under He flow, up to 723 K. It was found that, upon heating above 473 K, methoxy oxidized to methylenbisoxi (H2COO) and, then, to formate (HCOO) species, and traces of dimethyl ether were also detected. Surface formate species further decompose to give CO(g) and CO2(g) at temperatures higher than 573 K, with the concurrent generation of OH and H species over the surface, which react toward H2(g). It is suggested that the CO2 production implies the removal of lattice oxygen, generating a surface oxygen vacancy, which can be restored by water molecules from the gas phase. Thus, gallia can be envisaged as a promising support for the steam reforming of methanol, as long as a (noble) metal officiates/ acts as a rapid H2 releaser from the surface.